Clinical characteristics of tumor lysis syndrome in childhood acute lymphoblastic leukemia - Xue, Yao (Sci Rep, 2021)
Tumor lysis syndrome (TLS) is a common and fatal complication of childhood hematologic malignancies, especially acute lymphoblastic leukemia (ALL). The clinical features, therapeutic regimens, and outcomes of TLS have not been comprehensively analyzed in Chinese children with ALL. A total of 5537 children with ALL were recruited from the Chinese Children’s Cancer Group, including 79 diagnosed with TLS. The clinical characteristics, treatment regimens, and survival of TLS patients were analyzed. Age distribution of children with TLS was remarkably different from those without TLS. White blood cells (WBC) count ≥ 50 × 10(9)/L was associated with a higher risk of TLS [odds ratio (OR) = 2.6, 95% CI = 1.6–4.5]. The incidence of T-ALL in TLS children was significantly higher than that in non-TLS controls (OR = 4.7, 95% CI = 2.6–8.8). Hyperphosphatemia and hypocalcemia were more common in TLS children with hyperleukocytosis (OR = 2.6, 95% CI = 1.0–6.9 and OR = 5.4, 95% CI = 2.0–14.2, respectively). Significant differences in levels of potassium (P = 0.004), calcium (P < 0.001), phosphorus (P < 0.001) and uric acid (P < 0.001) were observed between groups of TLS patients with and without increased creatinine. Laboratory analysis showed that older age was associated with a higher level of creatinine. Calcium level was notably lower in males. WBC count, lactate dehydrogenase, and creatinine levels were significantly higher in T-ALL subgroup, whereas procalcitonin level was higher in B-ALL children. Older age, infant, a higher level of WBC and T-ALL were risk factors TLS occurrence. Hyperleukocytosis has an impact on the severity of TLS, while renal injury may be an important feature in the process of TLS.